Investigation of membrane protein—protein interactions using correlative FRET-PLA - Daniel Ivanusic; Magdalena Eschricht; Joachim Denner (BioTechniques, 2014)
Fluorescence resonance energy transfer (FRET) analysis and the recently developed proximity ligation assay (PLA) are widely used to study protein—protein interactions in situ. We have developed correlative FRET-PLA to monitor interactions between membrane proteins that frequently cause problems in confirmatory co-immunoprecipitation assays. Correlative FRET-PLA is particularly aimed at delivering robust and reliable results and is useful for investigating protein—protein interactions.